Slang as a Communication Strategy Employed by Jay and Jake of ENHYPEN in the Daebak Show Podcast - Qodriyati, Nurul Lailatul; Firdaus, Moh Iqbal; Anggraini, Diah Retno (Universitas Islam Negeri Palopo, 2025)
This study examines the use of English slang by Jay and Jake from Enhypen during their guest appearance on Eric Nam’s Daebak Show Podcast. Employing a descriptive qualitative approach, it investigates the morphological forms, semantic shifts, and pragmatic-social functions of slang terms used in the podcast. The primary data comes from the episode titled “ENHYPEN’s JAY & JAKE had ‘FATE’ to join Eric Nam | DAEBAK SHOW S3 EP12,” released on August 8th, with a duration of 52 minutes. The analysis focuses on spontaneous, informal English expressions from the idols, revealing how slang terms such as